Effects of different zinc oxide sources on weanling pig growth performance - J C Woodworth; J T Sawyer; C A Maxwell; Michael D Tokach; Jim L Nelssen; Robert D Goodband (Kansas Agricultural Experiment Station Research Reports, 1999)
A total of 192 pigs (initially 13.61b and 18 d of age) were used in a 27-d growth assay to determine the effects of different ZnO sources on weanling pig growth performance. The four experimental treatments consisted of a control diet or three diets containing Zn from ZnO from one of three different sources. For the entire trial, no differences occurred in growth performance of pigs fed the different ZnO sources; however, all sources increased ADG and ADFI compared to pigs fed the control diet. Economics and ingredient availability should dictate which ZnO source to use in weanling pig diets to promote growth.; Swine Day, Manhattan, KS, November 18, 1999
Keywords: Swine day; 1999; Kansas Agricultural Experiment Station contribution; no. 00-103-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 841; Swine; Early-weaned pigs; Growth; Zinc oxide